Kritik terhadap Keadilan Formal ; Memahami Positivisme dan Modernitas dalam Pemikiran Fransiscus Budi Hardiman - Syah Awaluddin (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
Modern legal thought is often dominated by the positivism school, which emphasizes legal certainty through written rules and formal procedures. However, this approach often overlooks the substantial aspect of justice, namely the sense of justice that lives within society. Fransiscus Budi Hardiman, in his work Melampaui Positivisme dan Modernitas (Beyond Positivism and Modernity), offers sharp criticism of formal justice that focuses solely on legality without considering morality and human values. This study aims to analyze Hardiman’s thoughts in the context of criticism against positivism and its impact on legal life in Indonesia. Using a philosophical approach and a qualitative-descriptive method, this study finds that Hardiman encourages a reinterpretation of law that is not only legal-formal but also humanistic and contextual. This perspective is relevant in addressing various legal cases in Indonesia, which often reveal a gap between legal decisions and the public's sense of justice. This study is expected to contribute to the development of a legal theory that is more responsive and adaptive to social dynamics.